Characteristics on Simple Sentences of Simple Present Tense Made by the Seventh Grade Students of SMPN 7 Samarinda - Sinaga, Yunita (CV. Eureka Murakabi Abadi, 2025)
This research was intended to know the characteristics of simple sentences of simple present tense made by the seventh grade students of SMP Negeri 7 Samarinda. This study used descriptive design. The population of the research was the seventh grade students of SMP Negeri 7 Samarinda with the total number of the population was 288 students, and the sample members taken was 58 students. The instrument of this study was a written test in the form of transformational sentences. The main tools to analyze the data were illustrations, facts, or features and statements. The research revealed the following findings: The characteristics of simple sentences in simple present tense made by the seventh grade students of SMP Negeri 7 Samarinda were: (a) omitting suffixes –s/es on main verbs for singular subject in affirmative forms, (b) mis forming the main verbs in present tense, (c) mis forming tense in simple present tense, (d) misusing auxiliary do/does in negative and interrogative form, (e) ) omitting auxiliary do/does in negative and interrogative forms and (f) misadding the auxiliary be and will.